Attuning to the Digital: Inquiring into Our Teacher Educator Literacies Practices - Scheffel, Tara Lynn; McKee, Lori; Correia, Bethany (Language and Literacy / Langue et littératie, 2026)
This article reports on a collaborative S-STEP where the authors, in response to the LLRC 2024 Preconference Call, attuned to digital media within their instructional practices in elementary English Language Arts (ELA) methods courses. This inquiry engaged with posthumanist theories of agential realism and concepts of entanglement and intra-actions. Findings for this paper come from an agential cut focused on a set of reading-focused literacy centers. The findings show the digital-in-practice, where digital media were always in relation to other human and non-human elements. Through its consideration of these intra-actions, this S-STEP illuminates elements of teaching and research practices and identifies implications for each.